2014
DOI: 10.1249/mss.0b013e3182a75ff2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Aerobic Exercise on Vaccine Efficacy in Older Adults

Abstract: Acute moderate aerobic exercise was not immunostimulatory in healthy older men but may serve as a vaccine adjuvant in older women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 24 publications
0
42
0
1
Order By: Relevance
“…Long et al [15] examined whether acute moderate exercise can improve immune responses to pneumonia and half dose influenza immunization and found no enhanced responses to either of the vaccines. Ranadive et al [14] also reported no difference in antibody responses in older men. However, results were not uniform in men and women.…”
Section: Moderate Aerobic Exercisementioning
confidence: 93%
See 1 more Smart Citation
“…Long et al [15] examined whether acute moderate exercise can improve immune responses to pneumonia and half dose influenza immunization and found no enhanced responses to either of the vaccines. Ranadive et al [14] also reported no difference in antibody responses in older men. However, results were not uniform in men and women.…”
Section: Moderate Aerobic Exercisementioning
confidence: 93%
“…However, contrary findings to this also exist. Ranadive et al [14] studied the effects of acute moderate exercise on influenza vaccine effectiveness, suggesting that acute moderate exercise does not enhance the vaccine efficacy in older men. Similarly, Long et al [15] also reported that moderate intensity brisk walking has no effect on antibody responses to both influenza and pneumonia immunization.…”
Section: Introductionmentioning
confidence: 99%
“…The acute effects of various types of exercise has also been investigated in a number of studies (Edwards et al, 2006(Edwards et al, , 2008Campbell et al, 2010;Edwards et al, 2010Edwards et al, , 2012Long et al, 2012;Ranadive et al, 2014). Generally, these studies have been conducted with younger rather than older subjects and in most of these cases no benefits are observed.…”
Section: Moderate Exercisementioning
confidence: 99%
“…However, it has been shown that influenza vaccination did not lead to decreased titers when conducted immediately after physical activity and that acute exercise even increased antibody responses in pneumococcal vaccination [138141]. In another study in elite athletes, titers after hepatitis B vaccination were identical to the general population [142].…”
Section: Timing Of Vaccinationsmentioning
confidence: 99%
“…influenza), there is no major medical problem with vaccinating shortly after a competition to make the period of time to the next competition as long as possible. Acute exercise might even act as a weak adjuvant, increasing antibody responses slightly in some individuals [138, 139, 141, 143]. In contrast, the pain reaction following the vaccination was clearly diminished when vaccinating 6 h after activity compared with vaccination immediately or 24–48 h after activity [143].…”
Section: Timing Of Vaccinationsmentioning
confidence: 99%